X-ray detectors based on the radiolytic synthesis of metal nanoparticles - Nunes, Luiz Henrique dos Santos (2022)
X-ray beams are widely applied to diagnosis and treatment, since their properties related to the interaction with the tissues in the body are desirable to imaging and radiation therapy. For both applications, the dose assessment is of great importance, in order to achieve the best efficiency in the imaging/therapy avoiding the undesirable effects of the exposition to high doses. A lot of dosimeters have been developed to attend this requirement. In this context, the nanoparticle-based dosimeters are a good alternative to dose assessment, since they present advantages as tissue equivalence and simple instrumentation requirements. The main idea of a nanoparticle-based dosimeter is to synthesize the nanoparticle upon the irradiation, in order to correlate the dose with the absorbance band intensity of the nanoparticles, due to the LSPR phenomena. In this thesis, some dosimeters based on the radiolytic synthesis of silver and gold nanoparticles were developed, in order to measure the low doses involved in the radiation imaging and therapy with x-rays. The synthesis was carried out by different methods combining a chemical reduction with an irradiation procedure in order to successfully form the nanoparticles and correlate their concentration to the absorbed dose. The silver nanoparticles generated a multimodal dosimeter based on microfluidic synthesis of AgNP, that allows the detection of the dose by UV-vis and fluorescence spectroscopies, with sensitivities of 9.2 10-3 and 3.4 a.u./Gy for doses up to 0.75 Gy, which are remarkable results compared to the literature. Besides that, this technique provides some insights about the nanoparticles formation, including the control of the nucleation and growth processes. The dosimeter based on gold nanoparticles (AuNP) was found to be effective to assess doses up to 10 Gy. The study of the chemical and radiolytic parameters of the synthesis confirmed the generation of seeds by templating, with a further growth related to the irradiation, leading to a dosimeter with sensitivity of 0.07 a.u./Gy. The analysis of the UV-vis signal for different energies spotlighted that, at higher doses, the nucleation and formation of more nanoparticles is favored over the growth. Moreover, the size distribution was found to be an alternative way to analyze the dose, but its influence is limited to higher energies, in the order of 160 kVp beam quality.